ANALISA POTENSI KEDALAMAN BATUBESI DENGAN METODE GEOLISTRIK 3D DI GUNUNG MELATI KABUPATEN TANAH LAUT - Widyayanti, Meta; Wahyono, Sri Cahyo; Wianto, Totok (Jurnal Fisika FLUX, 2013)
ABSTRACT: Iron ore are boulders containing of iron deposition, which consists of Feand the rest is composed by other minerals. There are 15 locations of iron ore in SouthKalimantan, one of them is Gunung Melati. Iron mineralization is formed by the contactof metasomatik-sedimentary volcanic rocks, the pyroclastic rocks series. The depthâspotency of iron ore is obtained from measurements with a 3D geoelectric method ofpole-pole configuration that indicate iron oreâs location in 3.20 to 10.1 m depth, and 27.1to 63.4 m with resistivity values of iron ore which has been measured in 3167-3847Ohm.meter and the potency of iron ore was spread unevenly in large chunks of stone.The samples test with XRD and SEM EDS is done to determine the composition andthe effect of washing enrichment process. XRD test results showed the dominance ofthe mineral hematite (Fe2O3) of sample 1 is 75% and sample 2 at 69%. After theenrichment washing, compoundâs phase turned into magnetite (Fe3O4). Sample 1which had been washed with water was change into 77% and 83% after enrichmentwashing with HCl, while sample 2 were washed with water to 70%, washed with a 79%HCl. The test results with SEM EDS showed the increased levels of smoothness ofsurface structure and Feâs level. Samples in sequence from start to washing with waterthen HCl Feâs level is at 37.62%; 49.47% and 55.33%. The comparison of Fe contentfrom the test results with the relative age based on stratigraphy showed that relativelyolder sample 1 has a Fe content greater than sample 2 relatively younger age.Keywords: Iron ore, geoelectric, XRD, SEM EDS, stratigraphy